Algebra

posted by .

Two functions f and g are defined by
f:x = x^2 + 3
g:x = 2x+1

Find the function fg

• Algebra -

(x^2+3)(2x+1)
2x^3+x^2+6x+3

Similar Questions

1. Algebra HELP!

Consider the function h as defined. Find functions f and g so (f o g)(x)=h(x) h(x)=8/x^2+10 I think it is: h(x)=8/x^2+10 h(x)=8/x^2+10*x^2/x^2 h(x)=8/x^2+10x^2/x^2 h(x)=8+10x^2/x^2 h(x)=10x^2+8/x^2 h(x)=2(5x^2)+2(4)/x^2 h(x)=2(5x^2+4)/x^2
2. Algebra

Today I did a practice SAT problem. If the function ƒ is defined by ƒ(x) = 2x + 3, and if ƒ(a) = 11, what is the value of a?
3. Algaebra

Two functions f and g are defined by f:x = x^2 + 3 g:x = 2x+1 Find the function fg Please help and show all working out,i got the answer for it but i really don't understand it!!! Thank You
4. Algaebra

Two functions f and g are defined by f:x = 25 /(3x-2) g:x = x^2 Find the composite function Please show all calculations, thank you!
5. Algebra

Two functions f and g are defined by f:x = 25 /(3x-2) g:x = x^2 Find the composite function
6. Precalculus

The application of one function followed by the application of a second function to the result of the first as in F^-1(f(x)) is called composition of functions. The two functions need not be inverse of each other. In a diagram, the …
7. math

The application of one function followed by the application of a second function to the result of the first as in F^-1(f(x)) is called composition of functions. The two functions need not be inverse of each other. In a diagram, the …